2016
DOI: 10.1038/leu.2016.388
|View full text |Cite|
|
Sign up to set email alerts
|

A novel BCMA/CD3 bispecific T-cell engager for the treatment of multiple myeloma induces selective lysis in vitro and in vivo

Abstract: B-cell maturation antigen (BCMA) is a highly plasma cell-selective protein that is expressed on malignant plasma cells of multiple myeloma (MM) patients and therefore is an ideal target for T-cell redirecting therapies. We developed a bispecific T-cell engager (BiTE) targeting BCMA and CD3ε (BI 836909) and studied its therapeutic impacts on MM. BI 836909 induced selective lysis of BCMApositive MM cells, activation of T cells, release of cytokines and T-cell proliferation; whereas BCMA-negative cells were not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
183
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(190 citation statements)
references
References 29 publications
7
183
0
Order By: Relevance
“…Although spleen showed significantly higher accumulation of P-cadherin LP-DART compared to control LP-DART at 48 h and 96 h, the quantities were very low. short plasma half-life requires continuous infusion and frequent administration of the drug, compared to weekly or bi-weekly administration of Fc-containing bispecific molecules [23,24]. We also compared the exposure of P-cadherin LP-DART when administered intravenously or subcutaneously using FMT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although spleen showed significantly higher accumulation of P-cadherin LP-DART compared to control LP-DART at 48 h and 96 h, the quantities were very low. short plasma half-life requires continuous infusion and frequent administration of the drug, compared to weekly or bi-weekly administration of Fc-containing bispecific molecules [23,24]. We also compared the exposure of P-cadherin LP-DART when administered intravenously or subcutaneously using FMT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A CD19/CD3 bispecific antibody designed in the BiTE format, blinatumomab, was reported to be effective in patients with B-cell malignances, such as relapsed or refractory B-cell precursor acute lymphoblastic leukemia, chronic lymphocytic leukemia, and non-Hodgkin lymphoma [45][46][47]. The BCMA/CD3 bispecific T-cell engager induced myeloma lysis in vitro and in vivo [48,49]. Topp et al showed that treatment with AMG 420, a BCMA bispecific T-cell engager in the BiTE antibody construct, induced MRD-negative CR in a phase I study of 42 RRMM patients who had received a median of 4 (range 2-13) prior treatment lines [21].…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…Trudel et al recently reported their experience with what to our knowledge is the most well studied of these immunoconjugates, GSK2857916, and found that anemia, thrombocytopenia, and low‐grade corneal events were common (57%); however, the ORR was 60% in heavily pretreated patients . Bispecific antibodies targeting BCMA in combination with CD3 also are being actively investigated, with preliminary results demonstrating rates of response and toxicity profiles similar to those noted with other BCMA‐targeted immunotherapies . Other immunotherapeutic targets currently under active study include CD38, CD138, CD19, kappa light chain, NY‐ESO‐1, and SLAMF7.…”
Section: Introductionmentioning
confidence: 99%